JUDICIAL PRACTICE IN THE PROTECTION OF THE RIGHTS OF MINORS IN THE REPUBLIC OF UZBEKISTAN - Dusmurodova Dilnura Alisherovna (Scholar Express Journal, 2025)
The article examines the features and trends of judicial practice in the field of protection of the rights of minors in the Republic of Uzbekistan. The research is based on the analysis of current legislation, including the Constitution, Family Code, Criminal Code, the Law "On Guarantees of the Rights of the Child", as well as a number of regulatory acts such as Presidential Decrees, Resolutions of the Cabinet of Ministers, and documents of the Oliy Majlis. Special attention is paid to the implementation of the principle of "the best interests of the child" in the practice of courts of general jurisdiction, as well as to the identification of systemic problems such as the absence of specialized juvenile courts, shortage of professional personnel, and imperfections in law enforcement. Based on the analysis of specific judicial decisions, the article proposes measures to improve the judicial system and strengthen mechanisms for the protection of the rights of minors, including institutional and legislative initiatives
Keywords: rights of minors; judicial practice; Law